Harmony Unveiled: Sharia Law and Human Rights in Dubai's Justice - Mustafa, Cecep; Komalasari, Rita (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
Utilizing a literature review as the primary method, this study delved into the navigation of tradition and modernity within Dubai's criminal justice system. The methodology entailed a comprehensive review of existing scholarly works, legal documents, and reports pertaining to the subject matter. The analysis synthesized insights from various sources to examine the system's integration of international human rights values and Sharia law principles. Additionally, it explored mechanisms for defending minority rights and assessed perceptions of the system's fairness and effectiveness among different segments of the population. Through this literature-based approach, key findings emerged. Firstly, the majority of sources indicated that the system effectively balances international human rights standards with Sharia law principles. Secondly, specialized courts and legal aid provisions were identified as mechanisms for safeguarding minority rights. Lastly, while the system was generally perceived as providing adequate protection, opportunities for improvement, such as enhancing access to justice for marginalized groups, were highlighted. In conclusion, the findings suggest that the Dubai criminal justice system has successfully negotiated tradition and modernity, offering valuable insights for other jurisdictions. Nonetheless, further research is warranted to evaluate the long-term implications of these findings and to refine strategies for ongoing enhancement in response to evolving societal demands.